Effect of antihypertensive deprescribing on hospitalisation and mortality: long-term follow-up of the OPTiMISE randomised controlled trial - Sheppard, JP; Temple, E; Wang, A; Smith, A; Pollock, S; Ford, GA; Hobbs, FDR; Kenealy, N; Little, P; Lown, M; de Lusignan, S; Mant, J; et al. (Elsevier, 2024)
Background: Deprescribing of antihypertensive medications is recommended for some older patients with low blood pressure and frailty. The OPTiMISE trial showed that this deprescribing can be achieved with no differences in blood pressure control at 3 months compared with usual care. We aimed to examine effects of deprescribing on longer-term hospitalisation and mortality. Methods: This randomised controlled trial enrolled participants from 69 general practices across central and southern England. Participants aged 80 years or older, with systolic blood pressure less than 150 mm Hg and who were receiving two or more antihypertensive medications, were randomly assigned (1:1) to antihypertensive medication reduction (removal of one antihypertensive) or usual care. General practitioners and participants were aware of the treatment allocation following randomisation but individuals responsible for analysing the data were masked to the treatment allocation throughout the study. Participants were followed up via their primary and secondary care electronic health records at least 3 years after randomisation. The primary outcome was time to all-cause hospitalisation or mortality. Intention-to-treat analyses were done using Cox regression modelling. A per-protocol analysis of the primary outcome was also done, excluding participants from the intervention group who did not reduce treatment or who had medication reinstated during the initial trial 12-week follow-up period. This study is registered with the European Union Drug Regulating Authorities Clinical Trials Database (EudraCT2016-004236-38) and the ISRCTN Registry (ISRCTN97503221). Findings: Between March 20, 2017, and Sept 30, 2018, a total of 569 participants were randomly assigned. Of these, 564 (99%; intervention=280; control=284) were followed up for a median of 4·0 years (IQR 3·7–4·3). Participants had a mean age of 84·8 years (SD 3·4) at baseline and 273 (48%) were women. Medication reduction was sustained in 109 participants at follow-up (51% of the 213 participants alive in the intervention group). Participants in the intervention group had a larger reduction in antihypertensives than the control group (adjusted mean difference –0·35 drugs [95% CI –0·52 to –0·18]). Overall, 202 (72%) participants in the intervention group and 218 (77%) participants in the control group experienced hospitalisation or mortality during follow-up (adjusted hazard ratio [aHR] 0·93 [95% CI 0·76 to 1·12]). There was some evidence that the proportion of participants experiencing the primary outcome in the per-protocol population was lower in the intervention group (aHR 0·80 [0·64 to 1·00]). Interpretation: Half of participants sustained medication reduction with no evidence of an increase in all-cause hospitalisation or mortality. These findings suggest that an antihypertensive deprescribing intervention might be safe for people aged 80 years or older with controlled blood pressure taking two or more antihypertensives.